2012
DOI: 10.21273/jashs.137.3.127
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitric Oxide on Proline Metabolism in Cucumber Seedlings under Salinity Stress

Abstract: Nitric oxide (NO), an endogenous signaling molecule in plants and animals, mediates responses to abiotic and biotic stresses. This study was conducted in a nutrient solution to investigate 1) the effects of exogenous sodium nitroprusside (SNP), an NO donor, on free proline (Pro) and protein content; and 2) the enzymes involved in Pro metabolism [pyrroline-5-carboxylate synthetase (P5CS) and proline dehydrogenase (PDH)] in cucumber (Cucumis sativus) seedling leaves and roots u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 49 publications
(62 reference statements)
5
24
0
Order By: Relevance
“…1). This result is in agreement with the previous reports regarding salt-treated cucumbers (Du et al, 2010a;Duan et al, 2008;Fan et al, 2012;Shi et al, 2007). Duan et al (2008) suggested that cucumber seedlings most likely increase the protein level of antioxidant enzymes and the content of osmoticants to enhance resistance to salinity.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…1). This result is in agreement with the previous reports regarding salt-treated cucumbers (Du et al, 2010a;Duan et al, 2008;Fan et al, 2012;Shi et al, 2007). Duan et al (2008) suggested that cucumber seedlings most likely increase the protein level of antioxidant enzymes and the content of osmoticants to enhance resistance to salinity.…”
Section: Discussionsupporting
confidence: 93%
“…The physiological responses of cucumber seedlings to salt stress have been well characterized. Specifically, salt stress destroyed the steady-state balance of reactive oxygen species (ROS) in cucumber seedlings, resulting in the loss of relative water content and net photosynthetic rates as well as a decrease in plant growth rates (Du et al, 2010a;Duan et al, 2008;Fan et al, 2012;Shi et al, 2007). Therefore, studies on salt stress are important to further understand the developmental mechanisms affected by salt for cucumber production.…”
mentioning
confidence: 99%
“…The increased transcript level of the proline biosynthesis gene (OsP5CS2) in NO-pretreated seedlings of the susceptible genotype under saline conditions, indicates the role of NO in the production of proline, which plays a significant role in counteracting salt-induced osmotic stress [64]. NO-induced proline accumulation in response to salinity in other crop species-such as wheat [53], cabbage [52], chickpea [46], and cucumber [54]-are in agreement with the present study.…”
Section: No Enhances the Expression Level Of Oshipp38 Osgr1 And Osp5supporting
confidence: 91%
“…The other ameliorating effect of NO on abiotic stress is through the metabolism and production of osmolytes in plants [51]. NO triggered biosynthesis and accumulation of proline content was reported in wheat, cucumber, and Chinese cabbage against salt stress [52][53][54]. Therefore, considering the multifaceted role of NO under stress conditions in different species, this study was designed to evaluate the mitigation effect of NO on salt stress in susceptible and tolerant rice genotypes with regard to gene modulations and phenotypic response.…”
Section: Introductionmentioning
confidence: 99%
“…However, the role of NO and the relationship between NO and H 2 O 2 , in rootstock‐grafted (Rs‐G) cucumber seedlings in response to salt stress‐induced oxidative damage is still unclear. In a previous study, it was demonstrated that application of exogenous NO reduced the harmful effects of salinity on cucumber seedlings (Fan et al ). In the present study, we used NO scavenger and inhibitors [2‐(4‐carboxyphenyl)‐4,4,5,5‐tetramethy‐limidazoline‐1‐oxyl‐3‐oxide (cPTIO), tungstate and N w ‐Nitro‐ l ‐Arg methyl ester hydrochloride ( l ‐NAME)] as well as H 2 O 2 scavenger and inhibitor (DMUT and DPI) to investigate the relationship between NO and H 2 O 2 in grafted cucumber plants under Ca(NO 3 ) 2 stress.…”
Section: Introductionmentioning
confidence: 99%